Early social experience and individual differences in infants' joint attention - Gaffan, E. A. (2010)
Fifty-nine healthy infants were filmed with their mothers and with a researcher at two, four, six and nine months in face-to-face play, and in toy-play at six and nine months. During toy-play at both ages, two indices of joint attention (JA)-infant bids for attention, and percent of time in shared attention-were assessed, along with other behavioural measures. Global ratings were made at all four ages of infants' and mothers' interactive style. The mothers varied in psychiatric history (e.g., half had experienced postpartum depression) and socioeconomic status, so their interactive styles were diverse. Variation in nine-month infant JA-with mother and with researcher-was predicted by variation in maternal behaviour and global ratings at six months, but not at two or four months. Concurrent adult behaviour also influenced nine-month JA, independent of infant ratings. Six-month maternal behaviours that positively predicted later JA (some of which remained important at nine months) included teaching, conjoint action on a toy, and global sensitivity. Other behaviours (e.g., entertaining) negatively predicted later JA. Findings are discussed in terms of social-learning and neurobiological accounts of JA emergence.